1996
DOI: 10.1046/j.1365-2249.1996.119808.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of anti-glomerular basement membrane (GBM) antibodies with synthetic peptides

Abstract: Autoantibodies to the non‐collagenous (NC1) domain of the α3(IV)‐chain of type IV collagen are found in sera from patients with anti‐GBM nephritis. These antibodies have been shown to be pathogenic. In this study the antibody specificity has been investigated in patients with Goodpasture’s syndrome and from a patient with atypical anti‐GBM antibodies, recognizing the α1(IV)‐chain only. Overlapping synthetic peptides, covering the complete NC1 domains of the α1(IV)‐ and α3(IV)‐chains were used in sandwich ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…Levy et al (23) identified nine reactive regions on a3(IV)NC1, whereas their results were not confirmed by Hellmark et al (24). Given the different designs of overlapping peptides and the relatively small groups of patients, no conclusions could be drawn from these studies.…”
Section: Discussionmentioning
confidence: 88%
“…Levy et al (23) identified nine reactive regions on a3(IV)NC1, whereas their results were not confirmed by Hellmark et al (24). Given the different designs of overlapping peptides and the relatively small groups of patients, no conclusions could be drawn from these studies.…”
Section: Discussionmentioning
confidence: 88%
“…They bind a conformational epitope destroyed by denaturation or reduction of native α3(IV)NC1. The importance of the shape of the epitope presumably explains the different results reported from early studies of binding of patient sera to linear synthetic peptides [16, 17, 18]. Recently, studies in three laboratories on patient sera binding to α3(IV)NC1/α1(IV)NC1 recombinant chimeras have agreed that all patients have antibodies that recognize an amino-terminal epitope [19, 20, 21].…”
Section: Recognition Of the Goodpasture Antigen For Disease Initiationmentioning
confidence: 99%
“…However, a synthetic peptide encoding the B cell epitope failed to induce GN or anti-GBM Ab (11,25). Mapping linear epitopes or generating mAbs to native GBM with peptides was not successful, because the Abs reacted only with denatured GBM proteins or did not react with GBM at all (9,20,21,23,24). Using more sophisticated point mutation and other techniques, several studies demonstrated that the anti-GBM Abs are bound to threedimensional (3-D) conformation of native Ags (26 -29).…”
mentioning
confidence: 99%